1996
DOI: 10.1074/jbc.271.44.27280
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibitors of the Proteasome-dependent and Vacuolar Pathways of Protein Degradation in Saccharomyces cerevisiae

Abstract: We have studied whether various agents that inhibit purified yeast and mammalian 26 S proteasome can suppress the breakdown of different classes of proteins in Saccharomyces cerevisiae. The degradation of shortlived proteins was inhibited reversibly by peptide aldehyde inhibitors of proteasomes, carbobenzoxyl-leucinylleucinyl-leucinal (MG132) and carbobenzoxyl-leucinylleucinyl-norvalinal (MG115), in a yeast mutant with enhanced permeability, but not in wild-type strains. Lactacystin, an irreversible proteasome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
313
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 376 publications
(329 citation statements)
references
References 33 publications
(35 reference statements)
15
313
1
Order By: Relevance
“…To investigate specific proteolytic pathways that may be involved in the destruction of BRCA1 protein during heating, we tested several protease inhibitors for their ability to block the loss of BRCA1 during heat shock. MG132 is a potent inhibitor of the 26S proteasome, which strongly inhibits the classic ubiquitin/proteasomal degradation pathway (Lee and Goldberg, 1996). Whether MG132 (10 mM) was present during heat shock (421C Â 2 h) or for 6 h prior to as well as during heat shock, there was no recovery of the BRCA1 protein levels in either DU-145 cells (Figure 11a) or MCF-7 cells (data not shown).…”
Section: Structural Requirements For the Heat-induced Degradation Of mentioning
confidence: 83%
“…To investigate specific proteolytic pathways that may be involved in the destruction of BRCA1 protein during heating, we tested several protease inhibitors for their ability to block the loss of BRCA1 during heat shock. MG132 is a potent inhibitor of the 26S proteasome, which strongly inhibits the classic ubiquitin/proteasomal degradation pathway (Lee and Goldberg, 1996). Whether MG132 (10 mM) was present during heat shock (421C Â 2 h) or for 6 h prior to as well as during heat shock, there was no recovery of the BRCA1 protein levels in either DU-145 cells (Figure 11a) or MCF-7 cells (data not shown).…”
Section: Structural Requirements For the Heat-induced Degradation Of mentioning
confidence: 83%
“…Studies using catalytic site-specific mutants of yeast proteasome and site-specific inhibitors have demonstrated that the chymotrypsin-like activity primarily determines the rate of protein degradation (Craiu et al, 1997;Lee and Goldberg, 1996). Therefore, the inhibition of this activity probably has the most significant consequences for key processes involved in cell survival.…”
Section: Consequences Of Proteasome Inhibitionmentioning
confidence: 99%
“…The inner two rings contain the β subunits. Three of the β subunits (β1, β2, β5) contain the catalytic sites that perform distinct proteolytic activities (Craiu et al, 1997;Lee and Goldberg, 1996;Rock et al, 1994). These activities are classified as caspase-like (β1), trypsin-like (β2), and chymotrypsin-like (β5) as defined by cleavage after acidic, basic, or hydrophobic amino acids, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…To test the possibility that YkB is a general proteasome inhibitor, we examined the effects of YkB on ATP-dependent proteasome activity using Arabidopsis T-87 cells and an S. cerevisiae ise1 (erg6) strain expressing ubiquitin-␤-galactosidase fusion protein as proteasome substrate under the control of the GAL4 promoter (39,40). The ise1 yeast strain was chosen to preclude detoxification of the drug by pumping via multidrug resistance channels (41).…”
Section: Ykb Blocks Primary Auxin-responsive Gene Expressionmentioning
confidence: 99%